Optimisasi Konsumsi Daya Listrik dengan Implementasi Logika Fuzzy-Mamdani Menggunakan Simulasi Matlab - Ardiansyah, Muhammad Fadil; Lukita, Muhammad Bagas; Damanik, Dearma Alam; Saifudin, Aries; Nirmala, Endar (Teknik Informatika Universitas Pamulang, 2021)
Optimization of electrical energy with fuzzy logic to obtain optimal electrical power output requires several inputs, namely light intensity, room temperature, room area, and humidity. In this study, to get each variable, it must have a membership function to determine how much influence the value of the variable has on the output issued. For the light intensity variable, for example, the membership function is dark, dim, bright, and very bright with a range between 0 to 1600 Lux, then for the temperature variable, the membership function is cold, cool, warm and hot with a range of 0 to 50 degrees Celsius. , for the variable area of the room has a membership function of narrow, medium, medium, and wide with a range of 0 to 90 m2, and for the input variable humidity has a membership function of dry, ideal, and humid with a range between 0 to 100 RH. MATLAB as an application that can perform fuzzy logic calculations will produce an output variable, namely electric power has a weak, rather strong, and strong membership function with a range of 0 seconds/d to 110 watts.